Kesiapan Masyarakat Desa Mancagahar dalam Pengembangan Kawasan Wisata Pantai Sayang Heulang (Studi Di Kecamatan Pameungpeuk Kabupaten Garut) - Akhsan Mulki Abdillah; Ima Amaliah (UNISBA Press, 2023)
Abstract. Tourism development is one part of economic development in a country. One of the priority programs is the development of the Sayang Heulang beach tourism area in Mancagahar Village, Pameungpeuk District. This development program is a strategic development project for West Java province. The purpose of this study was to measure how far the level of readiness of the Mancagahar village community was in developing Sayang Heulang beach tourism. The research method used is quantitative research. In quantitative research, that is to answer the readiness stage by distributing questionnaires to respondents. To strengthen the answers from the results of distributing questionnaires by gathering information from respondents in the form of in-depth interviews (interviews). The results of the analysis are presented descriptively. The results of the analysis show the Readiness of the Mancagahar Village Community in the Development of the Sayang Heulang Beach Tourism Area which is based on the 5 dimensions of readiness at the initiation stage. This means that the community participates and is involved in the development of the Sayang Heulang Beach tourist area. At the initiation stage it is marked by the fact that most of the community understands enough knowledge, the leader holds the key in planning, the community is sufficiently involved in development activities, the community is sufficiently aware of existing problems, and resources have been allocated to deal with the problem. Abstrak. Pengembangan pariwisata merupakan salah satu bagian dari pembangunan ekonomi dalam suatu negara. Salah satu program prioritas yakni pengembangan kawasan wisata pantai Sayang Heulang di Desa Mancagahar Kecamatan Pameungpeuk. Program pengembangan ini merupakan proyek pembangunan strategis provinsi Jawa Barat. Tujuan penelitian ini yaitu untuk mengukur seberapa jauh tingkat kesiapan masyarakat desa mancagahar dalam pengembangan wisata pantai Sayang Heulang. Metode penelitian yang digunakan adalah penelitian kuantitatif. Dalam penelitian kuantitatif yaitu untuk menjawab readiness stage dengan cara menyebarkan kuesioner kepada responden. Untuk memperkuat jawaban dari hasil menyebarkan kuesioner dengan menggali informasi dari para responden dalam bentuk in-depth interview (wawancara). Hasil analisis disajikan secara deskriptif. Hasil analisis menunjukan Kesiapan Masyarakat Desa Mancagahar Dalam Pengembangan Kawasan Wisata Pantai Sayang Heulang yang didasarkan pada 5 dimensi kesiapan berada pada tahap initation. Artinya masyarakat ikut dan terlibat dalam pengembangan kawasan wisata Pantai Sayang Heulang. Pada tahap initation ditandai dengan sebagian masyarakat cukup memahami pengetahuan, pemimpin memegang kunci dalam perencanaan, masyarakat cukup terlibat dalam kegiatan pengembangan, masyarakat cukup mengetahui permasalahan yang ada, dan sumber daya telah dialokasikan untuk menangani masalah.